Aetiologies of liver cirrhosis among adult patients attending a hepatology clinic at Selangor, Malaysia - Chieng, Jin Yu; Pan, Yan; Liew, Chiat Fong; Mazawawi Muhammad,; Syed Anas Tamamulqomar Said Abu Hassan, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2022)
Liver cirrhosis is an important cause of morbidity and mortality. Our study aimed to describe the aetiologies of liver cirrhosis and its associated risk factors among adult patients attending the Hepatology Clinic, Serdang Hospital, Malaysia from 1st January 2010 to 30th June 2017. Aetiology was determined by patients’ medical history as well as biochemical and/or histological findings. The severity of the liver cirrhosis, together with the presence of complications and incidence of hepatocellular carcinoma were documented. A total of 357 adult patients were diagnosed with liver cirrhosis including 199 male patients (55.7%) and 158 female patients (44.3%), with a mean age of 54-year-old (range: 28–84 –year-old). The determined most likely causes of liver cirrhosis were chronic hepatitis B (N=145, 40.6%), chronic hepatitis C (N= 67, 18.8%), cryptogenic liver disorder (N= 63, 17.6%), alcohol (N=42, 11.8%), non-alcoholic fatty liver disease (N=25, 7.0%), and others (N=15, 4.2%). Chronic hepatitis B was predominant among Chinese whereas alcohol consumption was mainly found among Indians, and Hepatitis C-linked liver cirrhosis was highest among Malays. Majority of the patients had compensated cirrhosis with Child-Pugh A (N=221, 61.9%) at the time of diagnosis. 80.4% (N=287) of the cirrhotic patients had performed at least one endoscopy surveillance, with 28.6% (82/287) of them had endoscopic evidence of portal hypertension. 32.2% of patients had at least one hospitalization due to complication of cirrhosis. 41 patients (11.5%) had concurrent hepatocellular carcinoma during the follow up. Hepatitis B viral infection remains the most common cause of cirrhosis among patients attending Hepatology Clinic, Serdang Hospital.